The effect of silane treatment on processing characteristic and swelling behavior of polypropylene/recycled acrylonitrile butadiene rubber/rice husk powder composites - Ragunathan, Santiagoo; Hanafi, Ismail, Prof. Dr.; Kamarudin, Hussin, Brig. Jen. Dato' Prof. Dr. (Trans Tech Publications, 2011)
Link to publisher's homepage at http://www.ttp.net/